POLA DIET ANAK, SEBERAPA BESAR HUBUNGANNYA DENGAN STUNTING DI INDONESIA ? - Salma, Wa Ode; Alifariki, La Ode; Harleli, Harleli (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2021)
Indonesia is currently ranked fifth in the highest number of stunting cases in the world. Malnutrition is still one of the causes of the high stunting rate in Indonesia. This study aims to examine studies on stunting that have been carried out in Indonesia systematically. Five online databases, including Google Scholar, PubMed, Wiley Online Library, Proquest, and Science Direct, were searched to identify relevant studies. The search is performed on the Title and Abstract. The combination of keywords and Medical Subject Headings (MeSH) used: Dietary, Food pattern, Nutrition, Stunting, Children, under five, Indonesia. The entire study was conducted in several regions in Indonesia including East Java, Malang, Lamongan, Bogor, Yogyakarta, and Madura. The submitted studies are published in reputable international journals and in English. The included study design consisted of 3 cross-sectional, and 2 case-control. The age of stunted children involved in the six studies reviewed was 6 – 59 months. The diet of children with stunting as a whole does not show conformity with the standard of nutritional needs to support the growth of children. From the five studies studied, it can be seen that the consumption patterns of children in Indonesia are less varied, low in vitamin D intake, low in calcium, and phosphorus.